Invaginated duct to mucosa pancreaticojejunostomy reduce postoperative pancreatic leakage: A matched case-controlled study. Issue 49 (10th December 2021) - Yao, Guo-Liang; An, Meng-Jiao; Fan, Yong-Gang
Abstract : Abstract: Postoperative pancreatic leakage is an obstacle in pancreaticoduodenectomy, which always follows pancreaticojejunostomy (PJ) failure. Dozens of PJ procedures have been reported, and none have shown superiority over others. Therefore, the present study is conducted to assess the potential advantages of invaginated duct-to-mucosa (D-M) PJ. We retrospectively analyze the related data from patients who underwent pancreaticodedunostomy due to malignant tumors at the First Affiliated Hospital of Henan University of Science and Technology from January 2017 to August 2019. According to the different PJ procedures, the patients are divided into custom D-M group and invaginated D-M group. Matching by sex, age, pancreatic duct size, and pancreatic texture is performed. Pancreatic leakage and other complications are compared, and SPSS 16.0 is employed for analysis. A total of 48 pairs of patients are included. Patients in both groups has almost the same baseline characteristics in terms of sex ( P = 1.000), age ( P = .897), American Society of Anesthesiologists status ( P = .575), body mass index ( P = .873), pancreatic duct size ( P = .932), pancreatic texture ( P = 1.000) and tumor origin ( P = .686). No significant difference is observed in operative outcomes, such as operative duration ( P = .632), PJ duration ( P = .748), blood loss ( P = .617) and number of required transfusions ( P = .523). Pancreatic leakage is significantly decreased in the invaginated D-M group ( P = .005). The differences in other complications, such as bleeding ( P = .617), biliary leakage ( P = .646), pneumonia ( P = .594) and thrombosis ( P = .714), do not reach statistical significance. The postoperative hospitalization duration is almost the same for both groups ( P = .764). Invaginated D-M PJ may reduce pancreatic leakage following pancreaticoduodenectomy.